Pregunta
upstudy study bank question image url

For the piecewise function, find the values \( h(-8), h(2), h(5) \), and \( h(6) \) \( h(x)=\left\{\begin{array}{ll}-3 x-18, & \text { for } x<-6 \\ 5, & \text { for }-6 \leq x<5 \\ x+1, & \text { for } x \geq 5\end{array}\right. \) \( h(-8)=\square \)

Ask by Ellis Logan. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( h(-8) = 6 \), \( h(2) = 5 \), \( h(5) = 6 \), \( h(6) = 7 \).

Solución

To evaluate the piecewise function \( h(x) \) at the given values, we'll determine which piece of the function applies to each input and then compute the corresponding output. The piecewise function is defined as: \[ h(x)= \begin{cases} -3x - 18, & \text{for } x < -6 \\ 5, & \text{for } -6 \leq x < 5 \\ x + 1, & \text{for } x \geq 5 \end{cases} \] Let's evaluate each requested value: 1. **\( h(-8) \)** - **Determine the interval:** \( -8 < -6 \) - **Function to use:** \( h(x) = -3x - 18 \) - **Calculate:** \[ h(-8) = -3(-8) - 18 = 24 - 18 = 6 \] - **Result:** \( h(-8) = 6 \) 2. **\( h(2) \)** - **Determine the interval:** \( -6 \leq 2 < 5 \) - **Function to use:** \( h(x) = 5 \) - **Calculate:** \[ h(2) = 5 \] - **Result:** \( h(2) = 5 \) 3. **\( h(5) \)** - **Determine the interval:** \( 5 \geq 5 \) (i.e., \( x \geq 5 \)) - **Function to use:** \( h(x) = x + 1 \) - **Calculate:** \[ h(5) = 5 + 1 = 6 \] - **Result:** \( h(5) = 6 \) 4. **\( h(6) \)** - **Determine the interval:** \( 6 \geq 5 \) (i.e., \( x \geq 5 \)) - **Function to use:** \( h(x) = x + 1 \) - **Calculate:** \[ h(6) = 6 + 1 = 7 \] - **Result:** \( h(6) = 7 \) ### Summary of Results: \[ \begin{align*} h(-8) &= 6 \\ h(2) &= 5 \\ h(5) &= 6 \\ h(6) &= 7 \\ \end{align*} \]

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To find the values of \( h(-8) \), \( h(2) \), \( h(5) \), and \( h(6) \), we need to evaluate each using the given piecewise function. 1. For \( h(-8) \): Since \(-8 < -6\), we use the first piece, \( h(x) = -3x - 18 \). - \( h(-8) = -3(-8) - 18 = 24 - 18 = 6 \). 2. For \( h(2) \): Since \(-6 \leq 2 < 5\), we use the second piece, \( h(x) = 5 \). - \( h(2) = 5 \). 3. For \( h(5) \): Since \(5 \geq 5\), we use the third piece, \( h(x) = x + 1 \). - \( h(5) = 5 + 1 = 6 \). 4. For \( h(6) \): Since \(6 \geq 5\), we again use the third piece, \( h(x) = x + 1 \). - \( h(6) = 6 + 1 = 7 \). Now we can summarize our values: - \( h(-8) = 6 \) - \( h(2) = 5 \) - \( h(5) = 6 \) - \( h(6) = 7 \) So in conclusion: \( h(-8) = 6, h(2) = 5, h(5) = 6, h(6) = 7 \)

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad